The Civic Dimension in the Educational Development of University Students in the Spanish Context - Miguel Ángel Santos Rego; María del Mar Lorenzo Moledo (Universidad Autónoma de Baja California, 2010)
In this paper we defend a view on university that fosters students' civic learning, emphasizing the benefits for their learning development and job placement process. First, we consider the opportunity that the European Higher Education Area (EHEA) has brought in order to update the matter of values in the university context and to link civic education and transversality within the same learning process. Secondly, we analyze on the one hand students' attitudes and, on the other, their interpersonal relationship and communication skills, comparing them according to the subject area of the official degrees in course of study. This is a descriptive survey study that involved a representative sample of 1,347 Spanish university students and 40 official degrees, corresponding to the five major subject areas. This statistical analysis of data allows us to state that there are substantial differences depending on the subject area, being Social Sciences students those who distinguish themselves better when showing a higher level of competence.